DAMPAK Psl. 7 atas UU NO. 36 TAHUN 2008 TERHADAP PELAKSANAAN PMK NO. 137/PMK.05/2005 PADA PENGENAAN PPH PASAL 21ATAS PEGAWAI TETAP - Yulita Setiawanta (MEDIA, 2012)
Taxation Laws change frequently implicates the part of the pattern of self assestment System which adopted by the tax law in Indonesia. Especially the imposition of income tax article 21 about regular employee. The changes are also properly considered by the Government in order to fill the state income derived from non-oil and gas sector that has been the main source of the income, annually. A change in income tax article 21 of regular employees although not individually significant, but when added together aggregately with certain assumption, it will achieve considerable value. It has also been consciously recognized by government, however, if the assumption of obedience taxpayer increases and the number of taxpayers is also in a good growth, the state income tax also does not decline, but it will expected to increase. An individual taxpayer or a regular employee, especially who receive only from one main source of income becomes a little bit helped by the reduction of taxes that must be paid in each tax period.